Perception on Cyber Terrorism: A Focus Group Discussion Approach - Ahmad , Rabiah (Scientific Research, 2012)
Focus group discussion is an exploratory research technique used to collect data through group interaction. This tech-nique provides the opportunity to observe interaction among participants on a topic under this study. This paper con-tributes to an understanding on the cyber terrorism conceptual framework through the analysis of focus group discus-sion. The proposed cyber terrorism conceptual framework which was obtained during the qualitative study by the au-thors has been used as a basis for discussion in the focus group discussion. Thirty (30) participants took part in the focus group discussion. The overall results suggest that the proposed cyber terrorism framework is acceptable by the partici-pants. The present study supports our initial research that the cyber terrorism conceptual framework constitutes the fol-lowing components: target, motivation, tools of attack, domain, methods of attack and impact